Chapter 2 Literary and Cultural Hermeneutics - Jiao, Min (Taylor & Francis, 2023)
"Literary and Cultural Hermeneutics" applies the general principles of philosophical hermeneutics to develop principles for literary interpretations. Heidegger's ideas on language and existentialien will be addressed as they render understanding ontological and function in a fabric relationship (Bewandnisganzheit). Gadamer's concepts of preunderstanding and the historicality of interpretation are also central to this research. On this basis, it elucidates the philosophical, the historical, and the cultural dimension, as well as a fusion of horizons in literary interpretation.